2017
DOI: 10.1186/s13613-017-0332-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combination therapy using antithrombin and thrombomodulin for sepsis-associated disseminated intravascular coagulation

Abstract: BackgroundNo single anticoagulant has been proven effective for sepsis-associated disseminated intravascular coagulation (DIC). Thus, the concomitant use of antithrombin concentrate and recombinant thrombomodulin has been conceived. This observational study was conducted to investigate the efficacy and safety of this combination therapy.MethodsA total of 510 septic DIC patients who received antithrombin substitution were retrospectively analyzed. Among them, 228 were treated with antithrombin and recombinant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…In addition, we could not conduct a detailed analysis of respiratory function due to the limitations of the DPC database. Iba et al reported a significant improvement in 28-day mortality following AT + TM combination therapy in patients with sepsis-associated DIC 7 . Although our study was characterized by substantially longer observation periods and more subject hospitals, the differences between our findings and those of Iba et al 7 underscore the need for further research to explore the merits of AT + TM combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we could not conduct a detailed analysis of respiratory function due to the limitations of the DPC database. Iba et al reported a significant improvement in 28-day mortality following AT + TM combination therapy in patients with sepsis-associated DIC 7 . Although our study was characterized by substantially longer observation periods and more subject hospitals, the differences between our findings and those of Iba et al 7 underscore the need for further research to explore the merits of AT + TM combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the efficacy of anticoagulant therapy using rTM has been demonstrated for infection-induced DIC (1-4), with some reports describing the efficacy of combination therapy with rTM and AT (8). In Japan, DIC treatments using AT and/or rTM are common for patients with sepsis-induced DIC.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of antithrombin (AT) for DIC has also previously been reported (5,6), and treatment with rTM and AT recently played an important role in anticoagulant therapy for infection-related DIC in Japan (7). More recently, combination therapy with rTM and AT has been shown to be effective for DIC (8).…”
Section: Introductionmentioning
confidence: 99%
“…A large multinational phase III clinical trial was recently completed and the results scheduled for presentation at the end of 2018 (NCT01598831). The co‐administration of recombinant soluble thrombomodulin with antithrombin was associated with reduced mortality among patients with sepsis‐induced DIC without increasing the risk of bleeding (Iba et al , ). However, the use of recombinant soluble thrombomodulin is currently restricted to Japan.…”
Section: Further Considerations For Treatment Of Haemostasis In Sepsismentioning
confidence: 99%